Análise teórica de um sensor capacitivo não intrusivo para determinação de fração de vazio e velocidade de bolha alongada em escoamentos gás-líquido - Seifert, Anyele (2022)
This work presents analyzes of a non-intrusive capacitive sensor, which is applicable for determining the phase fractions flowing in a stagnant liquid and the elongated bubble velocity. The void fractions and the velocity in intermittent flows are of great importance, as they help establish operational parameters that can be applied in the industrial sector. The sensor was designed using conductive tapes fixed around a pipe, capturing data converted by an electronic circuit. Through this circuit, the capacitance values are transformed into frequency and, consequently, the period. The elongated bubble velocity was found by numerical simulation based on the literature theorem, varying for different angles. From the analysis of velocity and period, it is possible to numerically obtain the minimum distance that the pairs of electrodes must be allocated in the pipe, to optimize the development of the sensor.